Teachers’ Production of Code-Switching and Code-Mixing in Spoken Short Functional Texts at SMP N 10 Semarang - Winanta, Alin Anastasya; Susanto, Dias Andris; Sodiq, Jafar (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This study aims to determine the types of code-switching and code-mixing produced by teachers in spoken short functional texts, the dominant type, and the factors that influence it. This research uses a descriptive qualitative method. The data source was taken from the English teacher's speech in the classroom. The result of the study was 61 teacher utterances which included 37 utterances of code-switching (60.66%) and 24 utterances of code-mixing (39.34%). The teacher used 3 types of code-switching, namely inter-sentence code-switching, intra-sentence code-switching, and tag code-switching. Then it also uses 3 types of code-mixing, namely insertion code-mixing, alternation code-mixing, and congruent code-mixing. The dominant type of code-switching is inter-sentential code-switching 30 utterances (81.08%), and code-mixing is insertion 15 utterances (62.50%). The factor that influences the use of code-switching and code-mixing is the situation where students' ability in English is still lacking.